A convergent mechanism of sex determination in dioecious plants: Distinct sex-determining genes display converged regulation on floral B-class genes - Zhang, Xianzhi; Pan, Linsi; Guo, Wei; Li, Yongquan; Wang, Wencai (Frontiers in Plant Science, 2022)
Sex determination of dioecious plants have been broadly and progressively studied with the blooming of genome sequencing and editing techniques. This renders us a great opportunity to explore the evolution and genetic mechanisms underlining the sex determining system in dioecious plants. Here in this work, according to comprehensively reviewing advances of sex-chromosomes, sex-determining genes and floral MADS-box genes in dioecious plants, we proposed a convergent model that governs plant dioecy across divergent species. In this model, a cascade regulation pathway connecting sex-determining genes and MADS-box genes e.g. B-class genes in particular, was proposed. It is believable that this convergent mechanism of sex determination in dioecious plants will shed light on our understanding of genetic regulation and evolution of plant dioecy. Perspectives especially concerning the evolutionary pathway of plant dioecy were also suggested.